A novel composite nonlinear controller for stabilization of constant power load in DC microgrid - Xu, Qianwen (2020)
Transportation electrification involves the wide utilization of power electronics based dc distribution networks and the integration of a large amount of power electronic loads. These power electronic loads, when tightly controlled, behave as constant power loads (CPLs) and may cause system instability when interacting with their source converters. In this paper, a composite nonlinear controller is proposed for stabilizing dc/dc boost converter feeding CPLs by integrating a nonlinear disturbance observer (NDO)-based feedforward compensation with backstepping design algorithm. First, the model is transformed into the Brunovsky's canonical form using the exact feedback linearization technique, to handle the nonlinearity introduced by the CPL. Second, the NDO technique is adopted to estimate the load power variation within a fast dynamic response, serving as a feedforward compensation to increase the accuracy of output voltage regulation. Then a nonlinear controller is developed by following the step-by-step backstepping algorithm with strictly guaranteed large signal stability. The proposed controller not only ensures global stability under large variation of the CPL but also features fast dynamic response with accurate tracking over wide operating range. Both simulations and experiments are conducted to verify the proposed strategy.